Biotic risks to important tree genera under climate change in Europe - Hannes Warlo; Horst Delb; Axel Albrecht; Markus Kautz (Journal für Kulturpflanzen)
Understanding the response of forest pests to climate change is essential to assess the future resilience of forest ecosystems. By considering nearly 200 individual research studies, we reviewed the effects of increased temperature and drought on insects and pathogens in six important host tree genera in Europe. Pest performance measures reported in the studies were aggregated at the species level and combined with an assessment of its damage potential to calculate a biotic risk index for the affected tree genera. While warmer temperatures and lower water availability led to an overall increase in biotic risk, we observed a clear ranking among hosts, with Picea and Abies being the most affected, followed by Quercus, Pinus, Pseudotsuga and Fagus. Functional groups of pests contributed differently to the genus-specific biotic risk. Our findings will help to improve estimates of tree mortality under climate change and facilitate decision-making in forest management.